Mamakiah: A Local Wisdom-Based Character Building Strategy for Multiculturalist Ulama in Minangkabau - Azwar, Welhendri; Yurisman, Yurisman; Permatasari, Yuli Permatasari; Ulil Amri, Mufti Ulil Amri (Islam Realitas: Journal of Islamic and Social Studies, 2024)
This study explains the essence of mamakiah tradition, which is currently misunderstood by society, which simply sees mamakiah as begging for sadakah or alms and begging. This research was conducted on several surau that still carrie out the mamakiah tradition. This study uses qualitative approaches, such as conducting in-depth interviews with surau or madrasa leaders, as well as students studying at surau, including those who still embrace the mamakiah tradition and those who have abandoned it. Observations were also made on how the mamakiah process is carried out. This study found that mamakiah tradition was a religious expression in the past. However, in its development, this custom was used as a method for developing the mindsets (mental testing) of students learning in surau in order to become future ulama. At the same time, this tradition provided an opportunity for these students to implement their religious knowledge (kaji) into practice in Surau.